Utilisation of wood polysaccharides as sugars - Ishihara, Mitsuro (Les (Ljubljana), 1999)
In Japan, the forest covers approximately 25 million ha, that is, about two-thirds of total land area, with different forest types from sub-frigid conifer forest in the north to sub-tropical forest in the south. Over a few decades, however, the low-quality hardwoods which had been utilised as firewood and charchoal have not been used except raw materials for pulp and mushroom cultivation. The steaming process of hardwood was studied for utilisation of hardwood polysaccharides as sugars as a part of Biomass Conversion Program by the Japanese Government. The yield of xylan hydrolysate (mixture of xylose and xylooligomers) from various hardwood species on steaming was 14-22 % under optimized conditions. Acidic xylooligomers carryinga 4-O-methylglucuronic acid residue or a galacturonic acid residue comprised approximately 10 % of the xylan hydrolysate. The enzymatic hydrolysis of residual lignocellulose was attemped on a large scale using an apparatus for continuous hydrolysis with a recycle system of cellulases. Glucose was a dominant component of the reducing sugars produced: most of hemicellulose in hardwood could be separated by the procedure of steaming followed by extracting with water. Finally, an economic analysis of hardwood components utilisation process on a plant scale by the Japanese Forestry Agency was described
Keywords: les; polisaharidi; pridobivanje; celuloza; encimatska hidroliza